1987
DOI: 10.1149/1.2100458
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Aromatic Polyimides

Abstract: Polyimides derived from condensation of pyromellitic dianhydride with various diamines have been shown to be electrochemically active. Films of these materials coated on the surface of solid electrodes, immersed in electrolyte solutions of dipolar aprotie solvents undergo two distinct reversible redox processes, involving addition of one or two electrons per repeat unit. These processes can be carried out completely and stoichiometrically for films as thick as 20 ~m. Spectrophotometric studies and comparison w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
45
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 9 publications
16
45
0
1
Order By: Relevance
“…The anion radical of PMDA-ODA polyimide was observed at 720 nm by Haushalter and Smith [19] and it showed both visible and ESR spectra as evidence of a PMDA-ODA polyimide anion radical. It was confirmed in this study that the visible spectra peak is identical to an anion radical of PMDA-ODA polyimide by the absorption peak as well as identical shape of absorption peak corresponds to the ESR peak, derived from the anion radical of PMDA moiety of polymer backbone [20]. The photoreaction of ionic-bonded photosensitive polyimide by means of various spectroscopic techniques as shown in Fig.…”
Section: Time-resolved Spectroscopysupporting
confidence: 77%
“…The anion radical of PMDA-ODA polyimide was observed at 720 nm by Haushalter and Smith [19] and it showed both visible and ESR spectra as evidence of a PMDA-ODA polyimide anion radical. It was confirmed in this study that the visible spectra peak is identical to an anion radical of PMDA-ODA polyimide by the absorption peak as well as identical shape of absorption peak corresponds to the ESR peak, derived from the anion radical of PMDA moiety of polymer backbone [20]. The photoreaction of ionic-bonded photosensitive polyimide by means of various spectroscopic techniques as shown in Fig.…”
Section: Time-resolved Spectroscopysupporting
confidence: 77%
“…The first peak involves the reduction of the neutral form to the radical anion form, while the second one, at a more negative potential, is the reduction to the dianion state. The aromatic diimide group behaves as an electron acceptor, undergoing two independent, oneelectron redox reactions comparable to a quinone [48,49]. The CV response of PI in DMAc is different from DMSO.…”
Section: Electrochemistry Of Cocl 2 /Polyimide Hybrid Materialsmentioning
confidence: 99%
“…It was reported that KOH treatment produces carboxyl as well as amide bonding on dianhydride-p-phenylenediamine (BPDA-PDA) polyimide [18][19][20]. Moreover, partially amidized polyimide is more hydrophilic, and therefore more permeable, toward the ethylenediamine (EDA) activation solution treatment [21,22]. Wet chemical pretreatment of electroless-plated Ni on polyimide films can be used to improve the interfacial bonding [12,20,23].…”
Section: Introductionmentioning
confidence: 99%